MHD stagnation flow of nanofluid past a permeable shrinking surface with various conditions - Muhammad Hasri, Nurul ‘Izzati (2018)
The purpose of the present study is to analyze the effects of slip and heat source/sink on magnetohydrodynamic stagnation-point flow and heat transfer past a permeable shrinking surface with convective boundary condition. The velocity and temperature profiles are analyzed with respect to the involved parameter such as slip parameter, magnetic parameter, heat source/sink parameter, Brownian motion parameter, thermophoresis parameter, suction parameter, shrinking parameter, Prandtl number, Biot number and Lewis number. Using a similarity transformation, the governing partial differential equations are transformed into nonlinear ordinary differential equations and the numerical solutions are solved by bvp4c in Matlab software. The numerical results indicate that the velocity increases with the increase in the values of slip parameter and suction parameter. The temperature profile increases as the increase of the Biot number and heat generation parameter whereas the increases of the heat absorption reduce the temperature.